Synthesis and antidepressant-like action of 9-alkoxy-7H-furo[3,2-g]chromen-7-ones in mice - Deng, Xian-Qing; Wei, Cheng-Xi; Song, Ming-Xia; Quan, Zhe-Shan (Arzneimittelforschung, 2010)
The present study describes the chemical synthesis and pharmacological evaluation of a series of 9-alkoxy-7H-furo[3,2-g]-chromen-7-ones. The pharmacological results of these compounds show that nine of them, given orally, reduced the immobility time in the forced swimming test. The results of the open-field test further confirmed that these compounds possessed an antidepressant-like effect. In the 5-hydroxytryptophan induced head-twitch test, 9-(3-chlorobenzyloxy)-7H-furo[3,2-g]chromen-7-one (3m, 40 mg/kg p. o.) significantly increased the cumulative number of head twitches. This finding suggested that the antidepressant-like profile seems to involve the serotonergic system as underlying mechanism.
Keywords: Antidepressant; Forced swimming test; Furocoumarin; 5-Hydroxytryptophan; Open-field test; Psoralen, analogues